2017
DOI: 10.1364/oe.25.025036
|View full text |Cite
|
Sign up to set email alerts
|

Initial conditions for dissipative solitons in a strict polarization-controlled passively mode-locked Er-Fiber laser

Abstract: We report the dynamics of dissipative solitons in a ring cavity passively mode-locked fiber laser with a strict control of the polarization state. We study the relation between the polarization state of the pulses propagating in the cavity and the regimes of generation. We have found that at pulse ellipticities between 5° and 15°, the laser generates one bunch of pulses in the cavity, while at higher ellipticities the laser generates multiple bunches. At constant ellipticity we rotated the polarization azimuth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
1
25
1
Order By: Relevance
“…In the following the minimal transmission angle is referred to as 0° and the angle of maximal transmission is 100°. In our previously reported works used all-polarization control cavities [25][26][27]33] we experimentally found that the regimes of mode-locking operation depend on the polarization state in CW mode, before mode-locking is started. We will refer to this state as the initial polarization state.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In the following the minimal transmission angle is referred to as 0° and the angle of maximal transmission is 100°. In our previously reported works used all-polarization control cavities [25][26][27]33] we experimentally found that the regimes of mode-locking operation depend on the polarization state in CW mode, before mode-locking is started. We will refer to this state as the initial polarization state.…”
Section: Resultsmentioning
confidence: 84%
“…These properties of the twisted fiber allow a strict control of the polarization state in the laser cavity. Recently, we demonstrated stable and predictable switching between different regimes of generation in a mode-locked fiber ring laser where fiber twist was used to cancel residual birefringence [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Strict polarization control allows precise control of the switching characteristic, which in turn allows selecting the regime of operation and type of generated pulses, and also allows adjusting the pulse properties over a wide range through well-defined wave retarder adjustments [27,28]. In addition to figure-eight lasers, ring-cavity fiber lasers consisting of twisted fiber were also designed [29,30]. In this case, the mode-locking mechanism is provided by NPR taking place in the twisted fiber ring together with a polarizer inserted in the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to figure-eight schemes, including a PI-NOLM, strict polarization control in ring cavities allows adjusting the bias, slope, switching power, and dynamic range of the switching characteristic. Such schemes made it possible to relate each setting of the polarization state (ellipticity and azimuth) to a specific mode of operation of the laser (polarization mapping) [29]. In one setup, precise polarization adjustments allowed selecting among as much as 10 different regimes, which encompass single-or dualwavelength operation, solitons, NLPs, or hybrid soliton-NLP emission, in a well-defined and repeatable way [30].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we demonstrated stable and predictable switching between different regimes of generation in a mode-locked fiber ring laser where fiber twist was used to cancel residual birefringence [21]. In the present work we propose and investigate a method to realize the cancellation of excessive NPR in a long mode-locked fiber ring laser.…”
mentioning
confidence: 98%